Recombinant expression of glycerol-3-phosphate dehydrogenase using the Pichia pastoris system - Sanches Peres, Maristela de Freitas [UNESP]; Silva, Viviane Cristina [UNESP]; Valentini, Sandro Roberto [UNESP]; Gattas, Edwil Aparecida de Lucca [UNESP] (Elsevier B.V., 2010)
In the present study, the GPD2 gene from Saccharomyces cerevisiae, which codifies for the enzyme glycerol-3-phosphate dehydrogenase (GPDH), was cloned from the pPICZ-alpha expression vector and used with the purpose of inducing the extracellular expression of the glycerol-3-phosphate dehydrogenase under the control of the methanol-regulated AOX promoter. The presence of the GPD2 insert was confirmed by PCR analysis. Pichia pastoris X-33 (Mut(+)) was transformed with linearized plasmids by electroporation and transformants were selected on YPDS plates containing 100 mu g/mL of zeocin. Several clones were selected and the functionality of this enzyme obtained in a culture medium was assayed. Among the mutants tested, one exhibited 3.1 x 10(-2) U/mg of maximal activity. Maximal enzyme activity was achieved at 6 days of growth. Medium composition and pre-induction osmotic stress influenced protein production. Pre-induction osmotic stress (culturing cells in medium with either 0.35 M sodium chloride or 1.0 M sorbitol for 4h prior to induction) led to an increase in cell growth with sorbitol and resulted in a significant increase in GPDH productivity with sodium chloride in 24h of induction approximately fivefold greater than under standard conditions (without pre-induction). (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Glycerol-3-phosphate dehydrogenase (GPDH); Pichia pastoris; Heterologous protein expression